Production of concentrated inocula from the microalgae Nannochloropsis oculata - Sales, Rafael; de Souza-Santos, Lília Pereira (Aquaculture international, 2020)
Aquaculture farms, such as the ones that produce mollusks, marine fish, and shrimp, require a constant supply of microalgae biomass as feed. Microalgae cultures are subject to failures in continuity; therefore, concentrated inocula could be used during episodes of crashes to reestablish the production of microalgae biomass. For this reason, the present work evaluated a concentrated inocula of the microalgae Nannochloropsis oculata harvested by flocculation and stored in a refrigerator with additives (vitamin C or citric acid) and without additives. Sensorial analysis (color and odor), protein content, cell integrity rate, cell resuspension rate, and culture growth parameters (maximum cell density and growth rate) were estimated for 15 weeks. The concentrates with citric acid presented an alteration in the color aspect at the 11 th week of storage. No differences were seen in the protein content and cell integrity rates either between storage methods or storage weeks. In sum, the use of additives did not significantly influence the growth performance of any of the treatments, since their cells continued to reproduce throughout the entire trial period. In addition, the additives enhanced the cell resuspension rate of the concentrates. For that reason, the concentrated inoculum with vitamin C was selected as the best treatment.